Establishing the protocol of molecular study of butterfly (lepidoptera: nymphalidae) - Nur Alwanie, Binti Maruji (Universiti Malaysia Sarawak (UNIMAS), 2012)
Optimization of polymerase chain reaction (PCR) using two kinds of primers of gene cytochrome oxidase subunit I (COI), which are the universal primer and COI_2; was done for establishing the protocol of molecular study of Nymphalidae. Five parts of the nymphalids were extracted to determine which yield the DNA product. These parts were the head, thorax, abdomen, legs and antennae, and the extraction was done by using the CTAB method. The extraction for the part head, thorax and abdomen were successful. Dried and fresh specimens were also used in this study and both yield DNA extraction product. The parameters for the optimization were designed into three programmes. PCR gradient was run 15 times and only one sample sent for sequencing. The amplification of mtDNA of universal primer COI and COI_2 were tested to obtain the PCR products, of which the amplification of DNA using COI_2 shows a positive result. Percentage of the successful PCR was calculated and of the positive result, the percentages for both good and poor bands were also calculated to interpret the successfulness of the PCR optimization.